How various drugs affect anxiety-related behavior in male and female rats prenatally exposed to methamphetamine - Macúchová, Eva; Ševčíková, Mária; Hřebíčková, Ivana; Nohejlová, Kateryna; Šlamberová, Romana (International journal of developmental neuroscience, 2016)
Different forms of anxiety-related behavior have been reported after a single drug use of many abused substances, however, less is known about how males and females are affected differently from exposure to various drugs. Furthermore, chronic prenatal methamphetamine (MA) exposure was shown to predispose the animal to an increased sensitivity to drugs administrated in adulthood. Using the Elevated plus-maze test (EPM), the first aim of the present study was to examine how male and female rats are affected by acute drug treatment with subcutaneously (s.c.) administrated (a) MA (1mg/kg); (b) drugs with a similar mechanism of action to MA: amphetamine (AMP, 1mg/kg), cocaine (COC, 5mg/kg), 3,4-methylenedioxymethamphetamine (MDMA, 5mg/kg); and (c) drugs with different mechanisms of action: morphine (MOR, 5mg/kg), and Δ 9-tetrahydrocannabinol (THC, 2mg/kg). The second aim was to determine if prenatally MA-exposed (5mg/kg) animals show an increased sensitivity to adult drug treatment. The parameters analyzed were divided into two categories: anxiety-related behavior and anxiety-unrelated/exploratory behavior. Our results showed in female rats a decreased percentage of the time spent in the closed arms (CA) after MA, and an increased percentage of the time spent in the open arms (OA) after MA, AMP, and COC treatment, indicating an anxiolytic-like effect. In females, MDMA and THC treatment increased the percentage of the time spent in the CA. An increased percentage of the time spent in the CA was also seen after MOR treatment in females as well as in males, indicating an anxiogenic-like effect. As far as the interaction between prenatal MA exposure and adult drug treatment is concerned, there was no effect found. In conclusion, it seems that: (a) in some cases female rats are more vulnerable to acute drug treatment, in terms of either anxiogenic- or anxiolytic-like effects; (b) prenatal MA exposure does not sensitize animals to the anxiety-related effects of any of the drugs.
Keywords: stimulanty centrálního nervového systému; serotoninové látky; krysa rodu Rattus; mužské pohlaví; Central Nervous System Stimulants; zpožděný efekt prenatální expozice; Sex Factors; Male; Exploratory Behavior; estrální cyklus; Serotonin Agents; Estrous Cycle; N-Methyl-3,4-methylenedioxyamphetamine; Female; Methamphetamine; úzkost; analýza rozptylu; pátrací chování; Analgesics; Time Factors; ženské pohlaví; Rats; těhotenství; Maze Learning; N-methyl-3,4-methylendioxyamfetamin; Prenatal Exposure Delayed Effects; Animals; Analysis of Variance; sexuální faktory; zvířata; analgetika; methamfetamin; Pregnancy; bludiště - učení; časové faktory; Anxiety